2012
DOI: 10.5171/2013.369047
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Enterprise Business Intelligence: Case Study Approach

Abstract: Recently, Business Intelligence (BI) play an essential role particular in business areas. BI is particular important for enterprises and it enables manager to view business performance in convenient way and hence improve decision making. Despite knowing how important of BI implementation, many organizations still struggle to achieve this especially in the construction company. This paper proposes an Enterprise Business Maturity Model (EBI2M) and evaluates in the three construction company in Malaysia. Prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Management also needs to be part of the BI project and have knowledge of the business processes for BI benefits to be fully recognised and advocate for proper usage of BIS (Sahay & Ranjan, 2008). Many companies have developed an interest in BI but there has been growing concern over the success of BI usage (Chuah & Wong, 2012). Research has identified benefits of BIS to a company (Sahay & Ranjan, 2008), but having the BI systems in place does not necessarily imply proper usage of BI systems.…”
Section: The Research Problemmentioning
confidence: 99%
“…Management also needs to be part of the BI project and have knowledge of the business processes for BI benefits to be fully recognised and advocate for proper usage of BIS (Sahay & Ranjan, 2008). Many companies have developed an interest in BI but there has been growing concern over the success of BI usage (Chuah & Wong, 2012). Research has identified benefits of BIS to a company (Sahay & Ranjan, 2008), but having the BI systems in place does not necessarily imply proper usage of BI systems.…”
Section: The Research Problemmentioning
confidence: 99%
“…Also, many business intelligence solutions have failed due to the final users' lack of access and not effectively meeting the final users' needs. Business intelligence projects have also failed due to not considering activities at the organizational level, non-commitment of business supporters, disinclination or lack of access of business representatives, lack of skillful and trained staff, lack of business activity analyses, lack of understanding of the impact of acquired information on business profitability, and lack of using information by users and staff (Chuah and Wong 2013).…”
Section: Factors Affecting Business Intelligence Implementationmentioning
confidence: 99%
“…TDWI framework mengukur dengan 8 perspektif yaitu ruang lingkup, pendanaan, sponsor, value, arsitek, data, perkembangan serta hasil [20]. TDWI framework dan BIDM framework ini sangat baik dikombinasikan sehingga aspek penilaian pada manajemen perguruan tinggi menjadi lebih luas [20], [22].…”
Section: Bidm Frameworkunclassified